Influence of Accounts Receivable Accounting Information System on Accounts Receivable Internal Control: Study at a service company engaged in the sale and after-sales of vehicles in Bandung - Syafira, Salsa; Komara, Anton Tirta; Djuhara, Djadjun; Rusjiana, Jimmy (Acman: Accounting and Management Journal, 2023)
This research aims to examine the impact of the X variable, which is the accounts receivable accounting information system, on the Y variable, namely the Internal Control of Receivables, at a service company specializing in the sale and after-sales of vehicles located in Bandung. The present study employs two distinct research methods. The first method is descriptive, wherein data analyze through description without any intention of drawing conclusions that generalize to the public. The second method is verification-based, which involves testing the validity of a hypothesis through field data collection. The findings of a study on a service enterprise involved in the distribution and post-sale maintenance of automobiles in Bandung indicate that the accounts receivable accounting information systems (X) have been functioning satisfactorily, with a score of 3.05. Similarly, the Internal Receivables Control (Y) has been deemed sufficiently effective, scoring 3.12. The study's findings suggest a significant correlation between the Accounts Receivable Accounting Information System and Receivables Internal Control, with a correlation coefficient 0.710. Additionally, the study highlights the impact of the accounts receivable accounting information system on accounts receivable internal control. The study reveals that receivables significantly contribute to the overall variance in the dependent variable, as evidenced by the R square value of 50.4%. However, it is essential to note that a considerable proportion of the variance (49.6%) still needs to be explained and may be attributed to other factors not examined in the research, such as company policy.